THE ROLE OF MICROFINANCE IN WOMEN’S EMPOWERMENT IN THE HIMALAYAN REGION - Bhatt Tiwari, Nisha; Bisht, Prof. Padam S.; Singh, Prakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the role of microfinance in promoting women’s empowerment in the Himalayan region of Nepal, with a specific focus on women’s economic independence. Microfinance programs, which provide small loans, savings opportunities, and financial literacy training, have been identified as crucial tools for empowering women in rural areas. This research uses a descriptive approach to analyse the experiences of 80 women engaged in microfinance activities. Data was collected through a structured questionnaire covering personal demographics, business ownership, loan utilization, training received, savings behaviour, income generation, and empowerment indicators. Advanced analytical techniques, including Principal Component Analysis (PCA), K-means clustering, Multivariate Analysis of Variance (MANOVA), Regression Analysis, and Structural Equation Modelling (SEM), were employed to examine the relationships between microfinance factors and empowerment outcomes. The results indicate that business ownership, loan utilization, and training are significantly associated with enhanced decision-making, confidence, and self-esteem among the respondents. PCA revealed that empowerment is driven by a combination of financial autonomy, education, and social support. K-means clustering identified three distinct groups of women based on their empowerment levels, while MANOVA confirmed that microfinance participation significantly impacts empowerment. Regression analysis highlighted business ownership and training as the strongest predictors of women’s empowerment, with income generation acting as an important mediator. The SEM model further emphasized the importance of income and business ownership in driving empowerment, both directly and indirectly. This study underscores the importance of integrating microfinance services with comprehensive capacity-building programs to maximize women’s empowerment in the region. It also offers valuable insights for policymakers and microfinance institutions looking to enhance the effectiveness of their interventions aimed at empowering women.